2005
DOI: 10.1002/ijc.21366
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the p53 status in mucosal and cutaneous melanomas

Abstract: The abrogation of the function of the ''gatekeeper of the genome'', p53, is the most prevalent molecular alteration in solid human tumors. Regarding melanomas the involvement of p53 alterations is discussed controversially to date. In order to evaluate the status of p53 in detail, primary tumors and metastases of 63 sporadic cutaneous (CM) and mucosal (MuM) melanomas were examined by immunohistochemistry and sequence analysis of the entire coding region of the p53 transcript, i.e., exons 2 to 11. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 43 publications
1
37
0
2
Order By: Relevance
“…We also found positive staining for DNp63 in some samples showing reduced Akt activation, whereas low Akt activation is well correlated with low DNp63 levels. These results are in agreement with previous reports showing that DNp63 is overexpressed in the vast majority of HNSCC (Sniezek et al, 2004;Gwosdz et al, 2005;Thurfjell et al, 2005), and might indicate that, besides Akt, alternative pathways influence such overexpression. Although p53 may be actively involved in this process (Hildesheim et al, 2004), our data indicated that p53 is not relevant in the modulation of DNP63 expression (Figure 7).…”
Section: Discussionsupporting
confidence: 94%
“…We also found positive staining for DNp63 in some samples showing reduced Akt activation, whereas low Akt activation is well correlated with low DNp63 levels. These results are in agreement with previous reports showing that DNp63 is overexpressed in the vast majority of HNSCC (Sniezek et al, 2004;Gwosdz et al, 2005;Thurfjell et al, 2005), and might indicate that, besides Akt, alternative pathways influence such overexpression. Although p53 may be actively involved in this process (Hildesheim et al, 2004), our data indicated that p53 is not relevant in the modulation of DNP63 expression (Figure 7).…”
Section: Discussionsupporting
confidence: 94%
“…[12][13][14] In our study, we found no association with risk of CM when the genotypes of the two SNPs were combined. The effect of p53 Arg72Pro on melanoma remains controversial, with some studies reporting associations between melanoma and the PP genotype 17,19 and others reporting associations between melanoma and the RR genotype. 18,20 Moreover, here we report that the distribution of p53 Arg72Pro genotypes do not vary by age, gender or Breslow thickness.…”
Section: Discussionmentioning
confidence: 99%
“…The results have shown positive associations between the proline/proline (PP) genotype and disease risk for some tumor types (for example esophageal squamous cell carcinoma, lung cancer, renal cell carcinoma [12][13][14] but no association for other tumor types (for example colorectal cancer, breast cancer 15,16 ). The association between the p53 Arg72Pro polymorphism itself and melanoma risk is controversial, [17][18][19][20] with some studies showing associations between melanoma risk and the PP genotype, 17,19 but others showing increased melanoma risk with the arginine/arginine (RR) genotype. 18,20 In light of these findings, we examined the MDM2 SNP309 and p53 Arg72Pro genotypes to determine whether they could be linked to an increased CM susceptibility, age of cancer diagnosis and clinical pathological variables in an Italian population composed of women and men.…”
Section: Introductionmentioning
confidence: 99%
“…Gwosdz et al [33] reported p53 mutations in 57-58% of MM suggesting the role of non-UV related mechanisms. We found aberrant p53 protein expression in 21% of MM, and in contrast to cutaneous melanomas where p53 over-expression increases with disease progression and metastasis [32,[34][35][36][37], we found no significant difference between initial mucosal melanomas and recurrent/metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%